Conceptualising the service excellence and its antecedents: the development of the structural equation model / Yuhanis Abdul Aziz and Khairil Wahiddin - Abdul Aziz, Yuhanis; Wahiddin, Khairil (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2010)
Increasing and maintaining service excellence in the tourism and hospitality industry are known to enhance the customers’ satisfaction and could bring more profits to the organisations. This conceptual paper focuses on the antecedents of service excellence, in particular the relationship with service characteristics, empowerment of employees, service excellence, and its impact on the selected outcomes. Using the existing literature, a proposed structural equation model with its associated hypotheses is developed to explain the relationship between service experience antecedents and its associated outcomes. Hence, the proposed model provides an understanding of the inter-linkages among service excellence, its antecedents and the outcomes. It provides some clearer insights into the importance of managing customer service experience which can contribute to customer satisfaction as well as enhancing an organisation’s competitive advantage. This is a conceptual paper, thus empirical work is required to test various research propositions empirically. The implications for the practitioners are also discussed.